Monoamines, Insulin and the Roles They Play in Associative Learning in Pond Snails - Totani, Yuki; Aonuma, Hitoshi; Oike, Akira; Watanabe, Takayuki; Hatakeyama, Dai; Sakakibara, Manabu; Lukowiak, Ken; Ito, Etsuro (Frontiers in Behavioral Neuroscience, 2019)
Molluscan gastropods have long been used for studying the cellular and molecular mechanisms underlying learning and memory. One such gastropod, the pond snail Lymnaea stagnalis, exhibits long-term memory following both classical and operant conditioning. Using Lymnaea, we have successfully elucidated cellular mechanisms of learning and memory utilizing an aversive classical conditioning procedure, conditioned taste aversion (CTA). Here, we present the behavioral changes following CTA training and show that the memory score depends on the duration of food deprivation. Then, we describe the relationship between the memory scores and the monoamine contents of the central nervous system (CNS). A comparison of learning capability in two different strains of Lymnaea as well as the F1 cross from the two strains presents how the memory scores are correlated in these populations with monoamine contents. Overall, when the memory scores are better, the monoamine contents of the CNS are lower. We also found that as the insulin content of the CNS decreases so does the monoamine contents which are correlated with higher memory scores. The present review deepens the relationship between monoamine and insulin contents with the memory score.